CREATION OF AN INTERACTIVE EDUCATIONAL ENVIRONMENT IN PROFESSIONAL TRAINING OF FUTURE MEDICAL SPECIALISTS - MELNYCHUK, Iryna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
Abstract. The article emphasizes the relevance of using interactive technologies, forms and methods of training in the professional training of future medical specialists. The essence of interactive learning is revealed in the context of pedagogy of cooperation and active dialogic interaction of all participants in the educational process. In general, the dialogic nature of interactive learning contributes to clarifying the level of preparation of students, which is manifested in the formation of professional knowledge, abilities and skills of future specialists in the medical field. In an interactive educational environment, students have the opportunity to demonstrate their understanding of the purpose, essence, features, direction of professional functions. It is argued that in an interactive learning environment, students have the opportunity to gain relevant experience in the medical field. The acquisition of professional skills and abilities takes place in a safe learning environment, which is of particular importance in the training of future doctors and nurses. The use of interactive technologies and methods is aimed at creating an interactive educational environment in medical institutions of higher education. The interactive cooperation of all participants in the educational process is directed to the activation of students' intellectual activity. Participation in interactive exercises encourages future doctors to self-educate, to test optimal and effective professional actions in practical activities. The main features of interactive learning are specified. Such characteristics include the possibility of active communication of its participants to solve professional tasks; the use of various forms and methods of professional and communicative interaction of future doctors; purposeful reflection of the participants of the interactive educational process and evaluation of the results of interpersonal interaction. It is summarized that interactive learning is a technological process of cooperation between subjects of pedagogical interaction. Interactive learning is considered as an organized pedagogical process, the basis of which is a set of interconnected active interactions between the teacher and students. It is emphasized that the main function of the teacher in the conditions of interactive learning is to create an effective educational for the self-development of the future medical specialist and to correct this process.